A feasibility study investigating the risk of prediabetes among children in New Zealand - Tupai-Firestone R; Cheng S; Corbin M; Lerwill N; Pulu T; Latu L; Dunn H; Pulu V; Firestone J; Fuge K; Tapu-Ta’ala S; Gokhale P; et al. (Springer Nature Limited, 2025)
Prediabetes is a non-communicable disease (NCD) that is common in New Zealand (NZ), and it can lead to poor health. The aim of this study was to identify whether there is an increased risk of developing prediabetes among 11–13-year-olds, outside an organised screening programme. Consenting school aged children and their parents completed a series of screening questionnaires including dietary patterns, anthropometrics and socio-economic characteristics. Adapted Australasian Paediatric Endocrinology Guidelines (APEG) criterion was used to identify children at risk of developing prediabetes or have new onset prediabetes. Of the 276 participants, significant differences between Pacific, Māori and non- Māori non-Pacific children were evident among those who: were obese (BMI > 95th percentile); lived in overcrowded homes and in deprived areas. In our study, a large proportion of children (35%) were at risk of developing prediabetes. From our dietary analyses, we identified two distinct dietary patterns from among the children: (1) a diverse diet that included a wide range of foods, but was particularly high in sweet and savoury snacks, takeaway foods, and sugary drinks; and (2) a predominantly vegetarian diet rich in legumes. The study prevalence of prediabetes risk is indicative of childhood lifestyles, and we recommend early screening and better resourcing for promotion of healthy nutrition as preventative measures.